The TransForum Model: Transforming Agro Innovation Toward Sustainable Development - van Latesteijn, Henk.; Andeweg, Karin; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The TransForum Model: Transforming Agro-innovation Toward Sustainable Development presents new insights on how to use innovation for the complex challenge of sustainable development. Innovation has been at the heart of the positive agricultural developments in both production and productivity growth during the last decades. Due to the negative impact of these developments on the physical and social environment, a transformational change of the agricultural sector is needed to shift toward a more sustainable development. Changing the agro innovation system is necessary to bring this about. In this book, six years of experimenting with sustainable development in agriculture is translated into a set of principles and guidelines. Together these constitute The TransForum Model to deal with innovation and sustainable development. This book shows how different scientific disciplines contribute to this new mode of agro innovation.
Preface -- 1. The need for a new agro innovation system -- 2. Inventions for future sustainable development in agriculture -- 3. Organizing innovations and transitions -- 4. For or Against Innovation? The influence of images -- 5. Mobilizing consumer demand for sustainable development6. From motivating assumptions to a practical innovation model -- 7. Transforming agriculture: a new approach to stimulate sustainable development -- Appendix I. TransForum: stimulating innovation for sustainable development by learning by doing -- Action experiments -- Scientific research -- Learning projects -- Appendix II. Action experiments explicated -- Appendix III. Overview experiments & projects -- Action experiments -- Scientific research projects -- Learning projects -- Appendix IV.
Keywords: Life sciences; Agriculture; Sustainable development; Life Sciences; Agriculture; Sustainable Development